Ambrosia Bakery / Fatin Amirah Torji - Torji, Fatin Amirah (2020)
Based on course requirement of Fundamental of Entrepreneurship (ENT300), there has the case study that I have to complete. During the case study, I must choose and collect the information about the company to ensure I have the strength and accurate point to be included in the case study. So, I decided to contact the owner of Ambrosia Bakery which is Mr Liow to getting the information such as the bakery’s background, organizational structure, product marketing and operational strategy. Then I also make some analysis about the business entity using SWOT analysis which are strength, weakness, opportunities, and last but not least is threat. In addition, I also enable to identify about how an entrepreneur solve and develop the bakery.